Efektivitas Pembelajaran Daring pada Mahasiswa - Saskia Melia; Kireina Zaira Nur Alpiah; Zahraina Melati Resmaya; Sri Mulyeni (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine and compare various findings from previous research on the effectiveness of online learning among university students in higher education settings in order to obtain a comprehensive general conclusion. The research method employed is a literature review using a content analysis approach of scholarly publications published between 2019 and 2025. The data sources include relevant national and international journal articles focusing on online learning in higher education. The results of the review indicate that the effectiveness of online learning is influenced by three interrelated main factors. Psychological factors include learning motivation, students’ perceptions of online learning, and the emotional conditions experienced during the learning process. Pedagogical factors encompass lecturers’ creativity in designing learning activities, the selection of appropriate teaching methods, and the use of interactive and varied learning media. Meanwhile, technical or environmental factors include the availability and ease of access to learning platforms, the quality of internet connectivity, and supportive learning environments. Online learning offers several positive impacts, such as flexibility in learning time, cost efficiency, and enhanced student experience in utilizing digital technology. However, it also has the potential to generate negative effects, including boredom, stress, and difficulties in understanding course material when technical barriers are not resolved and learning activities are monotonous. Therefore, optimal management of psychological, pedagogical, and technical factors is essential to improve the effectiveness of online learning for university students.